Management Of Peri-Urban Areas In Tambang District - Feby Dwi Ananda; Muhammad Syafi’i; Zulkarnaini Zulkarnaini (Green Publisher Indonesia, 2026)
Background: The rapid urban expansion has caused significant changes in peri-urban areas, resulting in land-use conversion, increased population density, and environmental degradation. The peri-urban region in Tambang District is facing these challenges, with a noticeable decline in agricultural land and increased risks such as flooding. Objective: This study aims to analyze the existing conditions of peri-urban management in Tambang District, identify the priority factors influencing its management, and propose appropriate strategies for sustainable development. Methods: A quantitative approach using surveys, questionnaires, and structured interviews with local experts and community members was conducted to gather data on environmental, economic, and social aspects of peri-urban management. Results: The study found that urban sprawl has significantly impacted agricultural land and infrastructure. Key challenges include insufficient infrastructure, environmental risks like flooding, and the need for better integration of environmental, economic, and social factors in development plans. Conclusion: Effective peri-urban management in Tambang requires a balanced approach integrating sustainable development principles, proper land-use planning, and active community participation. The proposed strategies aim to mitigate environmental risks and enhance the socio-economic benefits for the community.